Analisis Implementasi Total Quality Management (TQM) Dalam Meingkatkan Kualitas Produk Pada Conneight Studio Kota Malang - Bintang Nurdiansyah Putra; Mulyono Mulyono; Soedjono Soedjono (Ebisnis Manajemen, 2024)
The influence of globalization in today's industry has increased the level of competition between companies, making it increasingly tight and competitive. A company's success is often measured by the quality of the products it produces. Total Quality Management (TQM) is a continuous process that aims to achieve better quality standards in meeting customer needs.This study aims to determine the implementation of TQM, product quality, and to determine the improvement of product quality at Conneight Studio in Malang City. The method used is descriptive analysis.Based on the results of the study, the implementation of TQM requires commitment from all members of the organization. In the printing sector, all employees must be involved in efforts to improve product quality. Training, developing a quality culture, and active participation of the entire team are the keys to creating an environment that supports continuous improvement in product quality. TQM enables printing companies to achieve significant improvements in product quality. Data-based performance measurement is an important aspect of TQM. By collecting and analyzing data on product quality, companies can identify problems, monitor progress, and implement appropriate corrective actions. Effective use of data helps companies make decisions based on facts and evidence and guides continuous improvement efforts.